The Expression of Inflammatory Genes Is Upregulated in Peripheral Blood of Patients With Type 1 Diabetes - Jin, Yulan; Sharma, Ashok; Carey, Colleen; Hopkins, Diane; Wang, Xiaoxiao; Robertson, David G.; Bode, Bruce; Anderson, Stephen W.; Reed, John Chip; Steed, R. Dennis; Steed, Leigh; She, Jin-Xiong (Diabetes care, 2013)
Our previous gene expression microarray studies identified a number of genes differentially expressed in patients with type 1 diabetes (T1D) and islet autoantibody-positive subjects. This study was designed to validate these gene expression changes in T1D patients and to identify gene expression changes in diabetes complications. RESEARCH DESIGH AND METHODS: We performed high-throughput real-time RT-PCR to validate gene expression changes in peripheral blood mononuclear cells (PBMCs) from a large sample set of 928 T1D patients and 922 control subjects. Of the 18 genes analyzed here, eight genes (S100A8, S100A9, MNDA, SELL, TGFB1, PSMB3, CD74, and IL12A) had higher expression and three genes (GNLY, PSMA4, and SMAD7) had lower expression in T1D patients compared with control subjects, indicating that genes involved in inflammation, immune regulation, and antigen processing and presentation are significantly altered in PBMCs from T1D patients. Furthermore, one adhesion molecule (SELL) and three inflammatory genes mainly expressed by myeloid cells (S100A8, S100A9, and MNDA) were significantly higher in T1D patients with complications (odds ratio [OR] 1.3-2.6, adjusted P value = 0.005-10(-8)), especially those patients with neuropathy (OR 4.8-7.9, adjusted P value <0.005). These findings suggest that inflammatory mediators secreted mainly by myeloid cells are implicated in T1D and its complications.